2008
DOI: 10.1128/jb.00658-08
|View full text |Cite
|
Sign up to set email alerts
|

CDP-Alcohol Hydrolase, a Very Efficient Activity of the 5′-Nucleotidase/UDP-Sugar Hydrolase Encoded by the ushA Gene of Yersinia intermedia and Escherichia coli

Abstract: Nucleoside 5-diphosphate-X hydrolases are interesting enzymes to study due to their varied activities and structure-function relationships and the roles they play in the disposal, assimilation, and modulation of the effects of their substrates. Few of these enzymes with a preference for CDP-alcohols are known. In Yersinia intermedia suspensions prepared from cultures on Columbia agar with 5% sheep blood, we found a CDPalcohol hydrolase liberated to Triton X-100-containing medium. Growth at 25°C was deemed opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 48 publications
(46 reference statements)
2
28
0
Order By: Relevance
“…The structure of FAD, consisting of an ADP nucleotide with 5′‐linkage to a riboflavin moiety (Fig. 1), is reminiscent of UDP‐sugars and CDP‐alcohols that have been reported to be substrates of E. coli UshA (Glaser et al ., 1967; Neu, 1967; Alves‐Pereira et al ., 2008). However, despite this similarity in substrate structure, E. coli UshA exhibits very low FAD hydrolysis activity (Alves‐Pereira et al ., 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structure of FAD, consisting of an ADP nucleotide with 5′‐linkage to a riboflavin moiety (Fig. 1), is reminiscent of UDP‐sugars and CDP‐alcohols that have been reported to be substrates of E. coli UshA (Glaser et al ., 1967; Neu, 1967; Alves‐Pereira et al ., 2008). However, despite this similarity in substrate structure, E. coli UshA exhibits very low FAD hydrolysis activity (Alves‐Pereira et al ., 2008).…”
Section: Resultsmentioning
confidence: 99%
“…1), is reminiscent of UDP‐sugars and CDP‐alcohols that have been reported to be substrates of E. coli UshA (Glaser et al ., 1967; Neu, 1967; Alves‐Pereira et al ., 2008). However, despite this similarity in substrate structure, E. coli UshA exhibits very low FAD hydrolysis activity (Alves‐Pereira et al ., 2008). In order to test whether S. oneidensis UshA has the ability to catalyse hydrolysis of FAD, we added sonicated extracts of wild‐type and Δ ushA cells to solutions of FAD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UshA was more recently found to have a novel, highly efficient CDP-alcohol hydrolase activity (20), and it may have a general role in utilization of external UDP-glucose and extracellular nucleotides (21). X-ray structures have shown that UshA is a monomer (22); however, in our analyses it appeared as a complex with a molecular mass of ϳ177 kDa.…”
Section: Whole Cell Protein Complexes Of S Flexneri Serotype 2amentioning
confidence: 99%